Pengaruh E-Commerce Sebagai Penjualan Produk UMKM (Boboko) Di Kecamatan Bandung - Dimas Fauzi Farhan; Egi Makmuri; Nurartanti Nurartanti; Rika Sundari; Riki Gana Suyatna (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
The development of the digital world today is very rapid, in fact progress every year cannot be avoided in the online world. This really affects all sectors, including the business world and the economic sector. One of the digital-based business sectors is e-commerce. The word e-commerce actually comes from English, namely electronic commerce or electronic commerce. And like trade that is carried out directly or face to face, e-commerce also includes the process of promoting, purchasing and marketing products. This research uses a qualitative approach with descriptive research. If the definition of a descriptive method is as follows: a method used to study a group of people, an object, a set of conditions, a system of thought, or a category of events at that time. a systematic, fact-based and precise description, picture or painting of the facts, character and connections of the phenomena studied. During the research and up to the interview and observation stage, the informant did not object to providing information to the researcher. The informants in this research are as follows:Abah (informan) The first informant was an informant named Abah. This Abah was the first informant that researchers were able to interview and observe directly at the location. This is done directly so that you know and see directly how to make it, the process and the final result of the boboko craft. Based on the results of the discussion and explanation above, it can be concluded that, E-commerce is a very easy sale nowadays, which can be accessed by everyone throughout the world who understands the challenges of e-commerce. In contrast to this research, they want to sell their handicrafts via e-commerce / shop, but there are many obstacles that they don't understand, from the flow of creating an account, marketing and the process of sending the goods they want to sell.